An Analysis of a Child Called ‘It’ by Dave Pelzer from Family Systems Theory Perspective - Hafizha Fitriyantisyam (Universitas Pendidikan Indonesia (UPI), 2018)
Child abuse has a major and long lasting effect on children’s lives. Besides leaving horrible memories, the child abuse also affects the relationships among family members. This paper analyses a novel which consists of child abuse entitled A Child Called ‘It’ by Dave Pelzer whos aim is to see how the concepts of Family Systems Theory are realised in the issue of child abuse. Based on Family Systems Theory, there are four concepts found in the issue of child abuse. Two concepts, which are family projection process and nuclear family emotional process, are the triggers of child abuse. Two other concepts of Family Systems Theory, which are triangling and differentiation of self, are the factors that perpetuate child abuse. Thus, this paper concludes that the concepts of Family Systems Theory are realised in four concepts: family projection process, nuclear family emotional process, triangling, and differentiation of self. Keywords: child abuse, Family Systems Theory, and family relationships